Sosialisasi dan Aktivitas Seni sebagai Upaya Preventif dalam Melindungi Kesejahteraan Psikologis Kelompok Masyarakat Lansia di Dusun Ngunut Kidul, Gunungkidul - Jopingkan, Christabela; Kastuhandani, Fidelis Chosa (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
As the elderly population continues to grow, it is evident that older adults experience a series of risks to their psychological well-being, including loneliness, negative attitudes toward their declining physical condition, stress, and psychiatric disorders (such as anxiety, depression, and bipolar disorder). This condition is reflected in the significantly higher suicide rate among individuals aged 60 and above compared to other age groups. As a form of community service, a program was organized targeting the elderly community. The program involved education sessions with participatory art-based activities (weaving) that aimed to promote greater awareness about psychological well-being by increasing knowledge and involvement in art-based activities, enabling participants to experience the benefits firsthand. The activity took place on Tuesday, July 1, 2025, in Dusun Ngunut Kidul, Kelor Village, Gunung Kidul, Yogyakarta Special Region. Program effectiveness was assessed using two methods: survey and observation based on two main indicators: (1) participants' understanding of the importance of social, art, and physical activities, and (2) perceived benefits gained from the activities. The results show that the program was generally beneficial for participants by providing knowledge, experience, and potential for economic use. Nevertheless, the evaluation also reveals limited participation from elderly individuals and local residents. Therefore, it is recommended to make adjustments and modifications to the program to ensure greater impact on society. In the long term, the program model is expected to be replicated or adapted to ensure benefits on a wider scale.